227k views
0 votes
Simplify (y + 1)⁵ ÷ (y + 1)³​

User Koby Douek
by
5.7k points

2 Answers

0 votes

Answer:


given \\ \frac{ {(y + 1)}^(5) }{(y + 1) ^(3) } \\ as \: they \: have \: same \: base \\ {(y + 1)}^(5 - 3) \\ = (y + 1) ^(2) \\ or \: we \: can \: write \\ = (y + 1)(y + 1) \\ \\ hope \: it \: helps.

User Porsche
by
5.1k points
3 votes

Answer:

The answer is
y^2+2y+1

Step-by-step explanation:

- Properties of Exponent -


(a^m)/(a^n)=a^(m-n)

Our a is y+1

Our m is 5

Our n is 3


((y+1)^5)/((y+1)^3)=(y+1)^(5-3)\\(y+1)^2

- Multiply The Polynomial -

As for the Quadratic Polynomial and being squared, we use the following formula:


(x+y)^2=x^2+2xy+y^2

Our x is y

Our y is 1

Thus,


(y+1)^2=y^2+2(y)(1)+1^2\\(y+1)^2=y^2+2y+1

As our simplified, multiplied form is
y^2+2y+1

User Andrei Sedoi
by
5.7k points